Pregnancy complicated by fetal goiter following lung transplantation for idiopathic pulmonary arterial hypertension: A case study - Asuka Hamuro; Yoshifumi Kasuga; Saki Saito; Hiroshi Uchida; Takahiro Hiraide; Yohei Yamada; Takeshi Arimitsu; Hiroshi Date; Hiroyuki Fukushima; Mamoru Tanaka (Taiwanese Journal of Obstetrics & Gynecology)
Objective: We report a case of pregnancy following lung transplantation (LT) for idiopathic pulmonary arterial hypertension (IPAH) in Japan. Case Report: A female developed IPAH at 14 years of age and underwent a successful bilateral living-donor lobar LT from her parents at 19 years of age (gravida 2, para 0). At the age of 40 years, the patient became pregnant via artificial insemination. At 28 weeks of gestation, polyhydramnios and a fetal goiter were detected on transabdominal ultrasound. The patient was diagnosed with deep vein thrombosis and pulmonary embolism. The patient underwent emergency cesarean section to deliver a male neonate weighing 1340 g (−0.41SD) at 30 weeks of gestation, with an Apgar score of 5/5 (1/5 min). Conclusion: To our knowledge, this is the first reported case of a successful pregnancy following LT in Japan. Specialists should work together to manage pregnancies following LT.